The impact of information technology on knowledge creation: An affordance approach to social media. Issue 1 (2014) - ,; ,; ,
Abstract : Purpose – The purpose of this paper is to outline the potential of information technology, particularly social media and their affordances, in supporting knowledge creation within organizations.Design/methodology/approach – This is a conceptual paper which integrates the literature on both knowledge creation and social media.Findings – Social media may support knowledge creation by affording new types behaviors that were not possible with previous forms of computer‐mediated communication.Research limitations/implications – The paper contributes to theory development by integrating knowledge creation theory and addressing the role of technology, more specifically social media and their affordances, in the knowledge creation process.Practical implications – The results of the paper will help managers to understand which social media affordances support the distinct knowledge creation processes and target their use of technologies within the organization accordingly.Originality/value – The paper is of high theoretical and practical relevance. It bridges two previously unconnected literatures and, in doing so, provides an innovative perspective on how social media and their affordances may support knowledge creation.